DA'WAH COMMUNICATION BIL LISAN IN THE FDKI MENGAJI PROGRAM OF IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG - Azfa, Pani; Amrullah; Iqrom Faldiansyah; Gustin (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The implementation of da'wah (Islamic preaching) in the campus environment aims to develop spiritual values based on content and media. Activities are carried out in the form of religious, social, and community-based events. Da'wah institutions can grow effectively when strengthened by a sense of responsibility and loyalty from the institution’s management. However, challenges commonly faced by da'wah institutions include limited social outreach, lack of funding, and a small number of active members involved in the management. This research aims to describe verbal da'wah communication (da'wah bil lisan) in the